Corrosion and slurry erosion wear performances of coaxial direct laser deposited CoCrFeNiCu1-xMox high-entropy coatings by modulating the second-phase precipitation. (15th December 2021) - Wang, Jiakun; Chen, Yushan; Zhang, Yunhua; Dai, Wenying; Xu, Qian; Li, Weizhou; Liu, Yan
Graphical abstract: Highlights: A cost-efficient high-entropy alloy coating was designed based on the empirical knowledge and first-principles calculation. The CoCrFeNiCu1-x Mox coatings were successfully synthesized on duplex stainless steel by coaxial direct laser deposition technology following the expected design. The corrosion and slurry erosion wear mechanisms were clarified based on the experimental results and DFT calculation. Nanoscale second-phase precipitation can balance the corrosion resistance and mechanical property of high-entropy alloy coatings. Abstract: Developing high-entropy alloy (HEA) coatings with preferable properties for severe environments is a promising and cost-efficient way. In this work, an original HEA CoCrFeNiCu1-x Mox coatings were designed on-demand and successfully prepared on duplex stainless steel (DSS) through coaxial direct laser deposition technique. The first-principles calculation based on the density functional theory was employed to calculate the characteristics of materials. The results showed that the uniformly distributed Cu could stabilize the face-centered cubic phase structure, hinder the transfer of point defects, and activate the cathode. The synergistic effect of Mo and other HEA elements was beneficial in reducing the point defect density of the passive film, and an appropriate amount of Mo was contributed to grain refinement, solid solution strengthening, and precipitation strengthening of the coating. When the ratio of Cu to Mo is 1:3, a small number of nanoscales second sigma phase (Fe-Cr-Mo) appeared between ordered and disordered, which balanced the coating's corrosion and slurry erosion wear performances. Compared with DSS, the corrosion current density of CoCrFeNiCu0.25 Mo0.75 coating was reduced by nearly an order of magnitude, the impedance was increased by 2.5 times, and the erosion wear resistance was increased by 4 to 5 times.